Ecosystem Sustainability Assessment Using IUCN (Case Study: Dorook Basin) - Atefeh Teimoori; Seyed Mortza Seyedian; Hamed Rouhani; Reza Ahmadi (جغرافیا و پایداری محیط, 2018)
Sustainable Sustainability assessment using IUCN is a technical tool to understand and measure sustainable development. This technique allows comparing the existing conditions of the region with its ideal state, namely, full human development and a healthy and productive ecosystem. This approach simultaneously examines ecosystem sustainability and human sustainability. In this study, Dorook basin sustainability was assessed using IUCN method by 7 criteria and 17 indicators in the human section and 8 criteria and 18 indicators in the ecosystem section. In this study, Dorook basin was divided into two sub-basin called Aghcheshmeh and Ghaleghafeh. The measurements were done in each sub-basin separately. The results of analysis indicated that relation to sustainable human criterion and indicators, land use changes is the lowest score criterion. The criterion is moderate in education, skill and poverty in both sub-basins. By increasing youth employment, it can reduce dependency and improve the standard of poverty. The food security and nutrition standards are acceptable in both sub-basin. The criterion of justice and equality is poor and acceptable conditions in sub-basins of Aghcheshmeh and Ghaleghafeh, respectively. The final score of the Ghaleghafeh sub-basin is equal to 44 and the final score of the Aghcheshmeh sub-basin is 61. Generally the scores of both sub-basins indicate that sub-basins are in the medium range in terms of sustainability. The final score of the Dorook basin is 52, which is within the medium range. Investigating the indices showed that the area in terms of land use and erosion in comparison with other indicators is in a very bad situation and this index has the most negative effect in basin. Extended Abstract 1-Introduction According to FAO studies, about twenty million hectares of forest have been planted from 1995 to 1980 in developed countries, while two hundred million hectares of forest has been reduced in developing countries during this period. In contrast to other approaches, the IUCN method of Sustainability Assessment gives equal treatment to people and the ecosystem. It involves stakeholders in determining for themselves what sustainability means in their context. It uses, as its framework, a hierarchy of elements and objectives to translate the concept of sustainable development into concrete targets and measurable indicators. Thus making clear to all those involved what features everyone agrees contribute to measuring sustainability. The elements are designed to be tailored to local conditions and needs. The IUCN Sustainability Assessment Method is a user-focused process and thus can be used at international, regional, national, district or local scales. The IUCN Sustainability Assessment Method, in its full version, describes a process with seven stages. It is presented as a cycle because the assessment process is designed to allow updates that can show changes over time. According to the IUCN method widely used in different countries, in this study a set of measurements was determined according to the IUCN sustainability assessment method and organized based on issues and concerns related to forests. 2-Materials and Methods Dorook Catchment is the political section of Golestan province, Minoodasht city, and central section. There are 13 Villages in the basin. This catchment is the most important in Golestan province because of deforestation and loss of forest. A full Sustainability Assessment follows all seven stages in the assessment cycle. The general purpose of such assessment is to engage in reflection about sustainability, collect data for indicators, combine indicators and undertake analysis based on the indicators and use the data and process to assess priorities for action. Many indicator models use the Pressure-State-(Impact)-Response model to identify and organize indicators. Pressure three key types of indicators one covering the element's state, one showing pressures and one showing the way society is responding to the problem. Sustainability assessment primarily uses 'state' indicators, because in most cases, they are the most reliable measure of an element. Pressure indicators are useful in instances where measuring the pressure that one area is having on another is preferable – particularly cross border pollution, long-range transport of air or water pollutants and impacts on the global atmosphere. The use of response indicators is not encouraged in sustainability assessments, as it is often hard to link the state of an element with the responses society is undertaking to alleviate the problem. Three main components of ecosystems have been used including forests; water environment and climate were a total of 18 indicators and eight criteria. 7 criteria and 17 indicators were measured in human wellbeing. 3-Results and Discussion The results of analysis indicated that the relation to sustainable human criterion and indicators, land use changes is the lowest score criterion. The scores of Ghaleghafi and Aghcheshme are 30 and 0 respectively, indicating that the rate of land degradation is high. Changing of forest to agricultural land is the most important role in reducing stability in Dorook watershed. Education and skills criterion is medium in two sub-basin. Poverty criterion is medium in both sub-basin. In order to improve the conditions situation in the farms provide area youth by increasing employment rates, reducing dependency ratio. Food supply and food safety is in acceptable condition in both sub-basin. Justice and equality Criteria is in poor condition and acceptable in Aqcheshme and Ghaleghafi respectively. Score of soil conservation criteria in Aghcheshme sub-basin is 0 and in Ghaleghafi sub-basin is 28 that seems reasonable according to land use changes made in the following basins. Water status map shows that both sub-basin in good condition and is acceptable and In general, water ecosystem are in a much better situation than forest and human ecosystems. Weather and climate criteria in Aghcheshme sub-basins is in acceptable condition and in Ghaleghafi sub-basins is in the middle. 4-Conclusion Sustainable development indicators are expressing such interaction model between society and the environment. In general, Dorook basin ecosystems in Ghaleghafi sub-basins socio-economic performance and water criteria is in stable condition and in Aghcheshme sub-basins conservation and soil conservation are in unstable condition. The entire watershed is in the middle range and change conditions to improve sustainability need to promote appropriate policies.